Critical issues for employees in inter-municipal health care services: a multiple case study - Elisabeth Holen-Rabbersvik; Tom Roar Eikebrokk; Rune Werner Fensli; Elin Thygesen; Åshild Slettebø (BMC, 2018)
Abstract Background Traditional, hierarchical government structures have recently been challenged by increased complexity, fragmented services and heavy public demand. When healthcare services become fragmented and decentralised, they require redesign. Inter-municipal cooperation is a strategy to deal with current challenges and future demographic changes. Few studies exist that can help us conceptualize challenges regarding employment in this context and inform managers in the involved municipalities. This study aims to identify critical issues for employees in inter-municipal health care services and to elaborate on how and why these issues are experienced. Methods A multiple qualitative case study was conducted with data from interviews, observation studies, a participant workshop and inter-municipal healthcare service project documents and reports. The study involved two districts in Norway and six cases including 17 informants. First, a within-case analysis was conducted for all cases; second, a cross-case analysis was conducted in each district to examine replication, contrasts and extension to emergent findings; and, eventually, replicated findings in Districts 1 and 2 were analysed across districts. Results Three critical issues were identified: support, differences, and geographical distances. Employees working in teams experienced fewer challenges than did those working as isolated individuals. Conclusions Critical issues for employees represent an important aspect of inter-municipal cooperation, and additional research should be undertaken to inform future policy and practice.